Analisis Minat Belajar Murid Pada Mata Pelajaran Bahasa Indonesia Di Kelas VII-I SMP Negeri 4 Cimahi - Acep Sindi Sapari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to describe students' interest in learning Indonesian language subjects in class VII-I SMP Negeri 4 Cimahi in the 2024/2025 school year. The research method used is descriptive qualitative. The results showed that students in class VII-I at SMP Negeri 4 Cimahi already had an interest in learning in Indonesian language subjects in class. Supporting factors for student interest in learning are student motivation, encouragement from Indonesian language teachers, a conducive learning environment and adequate facilities and infrastructure. The inhibiting factors of students' interest in learning in class VII-I SMP Negeri 4 Cimahi are the conduciveness of the classroom environment, the lack of complete learning facilities and infrastructure and the busyness of individual students when learning Indonesian subjects. Efforts made by Indonesian language teachers are providing motivation and encouragement before Indonesian language learning takes place and ensuring a conducive learning environment. The conclusion of this research is a) interest in learning plays an important role in the achievement of Indonesian language learning objectives in class VII-I SMP Negeri 4 Cimahi 2) Most students in class VII-I SMP Negeri 4 Cimahi already have the criteria for interest in learning in class 3) factors that support student interest in learning in class VII-I SMP Negeri 4 Cimahi are learning motivation, encouragement from Indonesian language subject teachers, conducive environment and adequate facilities and infrastructure.